“Utilising ODL Technology in Case Based Teaching and Learning – Empowering Learners in OUM’s BBPS 4103” - Wardah Mohamad; Mansor Fadzil; Mohd Rizan Ruslan (2013)
Case studies have long been used in renowned business schools such as Harvard Business School in the United States and Curtin Business School in Australia as a tool to develop students’ critical thinking and analytical skills. The success of using case studies in capstone courses that cover a multitude of subjects have been well enumerated especially in the area of Strategic Management. However, most of these successes have been in conventional classrooms where discussions take place and students present their ideas and views in front of their peers. The Faculty of Business and Management, Open University Malaysia has taken this a step further by offering their BBPS4103 Strategic Management course fully-online where the teaching and learning is all done via videos and forums, supported with other learning materials, but with no face-to-face contact at all. This paper will present an overview of the project and how it has transformed the learning environment for our learners and resulted in a higher level of engagement. Learners are empowered to learn by themselves and can take learning a step further by being able to apply their critical thinking skills and theoretical concepts to a real-life case. Learning is done at their own pace through the use of on-line videos and a learner-centred forum. A comparison of the assessment results achieved by learners in the previous blended mode of learning and the new fully on-line mode is presented, along with an analysis of how the project has saved costs for the university. The paper concludes with recommended strategies for future improvements in utilizing ODL in case based teaching and learning. (Abstract by authors)